Innovative development of Ukraine in the context of international experience - Ковпак, Ельвіра Олександрівна; Тітомир, Олена Сергіївна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The dynamics of integrated assessments innovative development of Ukraine is described and the weaknesses and the strengths of the innovation system in Ukraine is identified based on the evaluation system of the Global Innovation Index.